2022
DOI: 10.1302/2633-1462.35.bjo-2021-0185.r1
|View full text |Cite
|
Sign up to set email alerts
|

What is the adult experience of Perthes’ disease?

Abstract: Aims Perthes’ disease is an uncommon hip disorder with limited data on the long-term outcomes in adulthood. We partnered with community-based foundations and utilized web-based survey methodology to develop the Adult Perthes Survey, which includes demographics, childhood and adult Perthes’ disease history, the University of California Los Angeles (UCLA) Activity Scale item, Short Form-36, the Hip disability and Osteoarthritis Outcome Score, and a body pain diagram. Here we investigate the following questions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The British Orthopaedic Surveillance Study reported 2-year outcomes from a prospective cohort of 371 children with Legg-Calvé-Perthes disease and found that 36% were treated with containment surgery but without evidence of improved outcomes 30 . More than 1,500 adult patients were surveyed about their childhood Legg-Calvé-Perthes disease, and 30% had had a surgery during adulthood, including 22% who had undergone at least 1 total hip arthroplasty 31 . However, a retrospective cohort study of hips with complex residual Legg-Calvé-Perthes disease deformities found that those that underwent combined periacetabular osteotomy and surgical dislocation had an 85% rate of preservation at the intermediate term 32 .…”
Section: Hipmentioning
confidence: 99%
“…The British Orthopaedic Surveillance Study reported 2-year outcomes from a prospective cohort of 371 children with Legg-Calvé-Perthes disease and found that 36% were treated with containment surgery but without evidence of improved outcomes 30 . More than 1,500 adult patients were surveyed about their childhood Legg-Calvé-Perthes disease, and 30% had had a surgery during adulthood, including 22% who had undergone at least 1 total hip arthroplasty 31 . However, a retrospective cohort study of hips with complex residual Legg-Calvé-Perthes disease deformities found that those that underwent combined periacetabular osteotomy and surgical dislocation had an 85% rate of preservation at the intermediate term 32 .…”
Section: Hipmentioning
confidence: 99%
“…Using a web-based platform, Mcguire et al collected 1182 responses to a questionnaire from patients of 45 different countries who developed LPCD in childhood. They found that 40% of respondents had undergone at least one surgical procedure during childhood while 22% and 30% underwent at least one total hip replacement and any type of surgery, respectively [ 24 ].…”
Section: Introductionmentioning
confidence: 99%